Penggunaan Metode Audi Lingual Dalam Meningkatkan Kemampuan Berbicara Peserta Didik dalam Bahasa Jepang - Afis Alhadi; Jehwae, Phaosan (Manna wa Salwa Foundation (Yayasan Manna wa Salwa), 2023)
The abstract should be in full reasoned italics at the beginning of the paper, with a single column like this, below the author information. Use the word